Zirconium boride-based multiphase ceramic electrode for electric arc furnace and preparation method of zirconium boride-based multiphase ceramic electrode

By using a combination of zirconium boride powder, zirconium carbide powder, silicon powder and tungsten powder in the electrode for arc furnace, combined with the vacuum induction sintering process, the problems of low wear resistance, fracture toughness, electrical conductivity and thermal conductivity of the electrode for arc furnace are solved, and a zirconium boride matrix composite ceramic electrode with excellent performance was prepared.

CN119569463AActive Publication Date: 2025-03-07WUHAN UNIV OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411546643.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing electrodes for arc furnaces have problems such as poor wear resistance, poor fracture toughness, low electrical conductivity and low thermal conductivity.

Method used

Mixed ball milling was performed using 85 to 95 wt% zirconium boride powder, 2 to 5 wt% zirconium carbide powder, 2.5 to 8 wt% silicon powder and 0.5 to 2 wt% tungsten powder, and then sintered in a vacuum induction furnace to form a zirconium boride-based composite-phase ceramic electrode.

Benefits of technology

The zirconium boride-based composite ceramic electrode produced for arc furnace has good wear resistance, excellent fracture toughness, high electrical conductivity and excellent thermal conductivity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a zirconium boride-based multiphase ceramic electrode for an electric arc furnace and a preparation method of the zirconium boride-based multiphase ceramic electrode. According to the technical scheme, firstly, zirconium boride powder, zirconium carbide powder, silicon powder and tungsten powder are mixed, ball-milled and dried, and composite powder is obtained; and carrying out compression molding and cold isostatic pressing molding on the composite powder to obtain a ceramic green body. And placing the ceramic green body in a vacuum induction furnace, and carrying out vacuum induction sintering to obtain the zirconium boride-based multiphase ceramic electrode for the electric arc furnace. The vacuum induction sintering process comprises the following steps: firstly opening a circulating water valve, then turning on a power supply of an induction furnace, under a vacuum condition, firstly heating to 800-900 DEG C, then heating to 1500-1600 DEG C, preserving heat, turning off the power supply of the induction furnace, and then turning off the circulating water valve. The zirconium boride-based composite ceramic electrode for the electric arc furnace, prepared by the invention, is good in wear resistance, excellent in fracture toughness, high in electric conductivity and excellent in heat conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of zirconium boride-based composite ceramic electrodes, and specifically relates to a zirconium boride-based composite ceramic electrode for an electric arc furnace and a preparation method thereof. Background Art

[0002] Electric arc furnace steelmaking is a steel production process that uses the high temperature generated by the electrode arc to recover scrap steel and melt raw materials. Compared with existing blast furnace steelmaking, electric arc furnaces have the advantages of low energy consumption, less environmental pollution and high flexibility, so they have occupied an increasingly important position in steel production.

[0003] In the current research on arc furnace electrode materials, graphite electrodes are widely used due to their good electrical conductivity and chemical stability. However, graphite electrodes have poor toughness and are prone to oxidation under high temperature and high pressure environments. They are also easy to wear due to their low hardness, which affects their service life. Therefore, finding electrode materials with better performance has become a research focus. Zirconium boride-based composite ceramics are expected to become an effective substitute for graphite electrodes due to their excellent thermal stability, high hardness, high electrical conductivity, and excellent thermal conductivity, and have attracted the attention of technicians in this field.

[0004] The patented technology of "A graphite electrode for electric arc furnace (CN201821619781.2)" improves the overall cooling effect of the graphite electrode and extends the service life of the graphite electrode. However, the low hardness of the graphite electrode leads to high wear and consumption.

[0005] The patented technology of "A graphite electrode for electric arc furnace (CN202021539191.6)" provides a simple and low-cost preparation process, but the fracture toughness of the prepared electrode is low.

[0006] The patented technology of "A graphite electrode for electric arc furnace (CN202021148051.6)" introduces inert gas through the ventilation channel to cool the graphite electrode body to reduce oxidation on the surface of the graphite electrode. The gas effectively forms gas turbulence inside the ventilation channel. Although the heat exchange efficiency is high and the cooling effect is good, the conductivity of the prepared graphite electrode is low.

[0007] A document (Yang BL, Kuang CL, Liu ZL, et al. Effect of nano-graphite on mechanical properties and oxidation resistance of ZrB2-SiC-graphite electrodeceramics[J]. Journal of Iron and Steel Research International, 2024, 31(6): 1502-1513.) proposed introducing nano-graphite into zirconium boride ceramic electrodes for electric arc furnaces. Although the fracture toughness is improved to a certain extent, too much graphite will lead to a decrease in the density of the zirconium boride material, resulting in a lower thermal conductivity of the ceramic electrode.

[0008] In summary, existing arc furnace electrodes have the following technical defects: poor wear resistance, poor fracture toughness, low electrical conductivity and low thermal conductivity. Summary of the invention

[0009] The present invention aims to overcome the shortcomings of the prior art and has the objective of providing a method for preparing a zirconium boride-based composite ceramic electrode for an electric arc furnace. The zirconium boride-based composite ceramic electrode for an electric arc furnace prepared by the method has good wear resistance, excellent fracture toughness, high electrical conductivity and excellent thermal conductivity.

[0010] To achieve the above purpose, the specific steps of the technical solution adopted by the present invention are:

[0011] Step 1: First, 85-95wt% of zirconium boride powder, 2-5wt% of zirconium carbide powder, 2.5-8wt% of silicon powder and 0.5-2wt% of tungsten powder are mixed, and then ball milled for 8-10 hours with a ball mill, and dried to obtain a composite powder.

[0012] Step 2: Pressing the composite powder into a shape under the condition of 100-120 MPa, and then cold isostatic pressing to obtain a ceramic body.

[0013] Step 3: placing the ceramic body in a vacuum induction furnace for vacuum induction sintering to obtain a zirconium boride-based composite ceramic electrode for an electric arc furnace.

[0014] The vacuum induction sintering process is as follows: first open the circulating water valve, then turn on the induction furnace power supply, and at a vacuum degree of 10 -2 ~10 -1 MPa, first heat to 800-900℃ at a power of 8-15kw, then heat to 1500-1600℃ at a power of 16-20kw, keep warm for 0.5-1.5h, turn off the power of the induction furnace, keep the circulating water valve open for 2-5h, and then close the circulating water valve.

[0015] The particle size of the zirconium boride powder is 1-3 μm; the purity of the zirconium boride powder is 99.9%.

[0016] The particle size of the zirconium carbide powder is 1-3 μm, and the purity of the zirconium carbide powder is 99%.

[0017] The particle size of the silicon powder is 1-5 μm, and the purity of the silicon powder is 99%.

[0018] The particle size of the tungsten powder is 1-5 μm, and the purity of the tungsten powder is 99.9%.

[0019] The ball milling process is as follows: the rotation speed is 600-800 rpm, the ball milling medium is anhydrous ethanol, the grinding ball material is zirconium oxide, and the mass ratio of grinding ball to mixed powder is 1-4:1.

[0020] The cold isostatic pressing process:

[0021] First, increase the pressure at the following rates: increase the pressure to 30-50MPa at a rate of 0.1-4MPa / s, increase the pressure to 60-80MPa at a rate of 0.1-5MPa / s, increase the pressure to 90-110MPa at a rate of 0.1-10MPa / s, increase the pressure to 120-140MPa at a rate of 0.1-6MPa / s, increase the pressure to 150-200MPa at a rate of 0.1-8MPa / s, and maintain the pressure for 3-5min;

[0022] Then reduce the pressure at the following rates in sequence: reduce the pressure to 120-140MPa at a rate of 0.1-5MPa / s, reduce the pressure to 90-110MPa at a rate of 0.1-6MPa / s, reduce the pressure to 60-80MPa at a rate of 0.1-8MPa / s, reduce the pressure to 30-50MPa at a rate of 0.1-5MPa / s, reduce the pressure to 2MPa at a rate of 0.1-5MPa / s, and unload to normal pressure.

[0023] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:

[0024] (1) The present invention makes full use of the high conductivity of the zirconium boride material itself, utilizes the reactivity of zirconium carbide powder, silicon powder and tungsten powder at high temperature, regulates the in-situ formation of zirconium-tungsten alloy, zirconium silicide and silicon carbide and other bonding phases between the zirconium boride powder particles, and synergistically improves the electrical conductivity and thermal conductivity of the zirconium boride-based composite ceramic electrode for electric arc furnaces. Therefore, the zirconium boride-based composite ceramic electrode for electric arc furnaces prepared by the present invention has high electrical conductivity and excellent thermal conductivity.

[0025] (2) The present invention utilizes the reaction between zirconium carbide powder, silicon powder and tungsten powder during vacuum induction sintering to form zirconium-tungsten alloy, zirconium silicide and silicon carbide in situ between zirconium boride particles, thereby strengthening the bonding between zirconium boride powder particles; and utilizes the volume deformation during the reaction process to adjust the pore structure between particles and the densification behavior of material sintering. Therefore, the zirconium boride-based composite ceramic electrode for electric arc furnaces prepared by the present invention has excellent fracture toughness and good wear resistance.

[0026] The boride zirconium-based composite ceramic electrode for arc furnace prepared by the present invention is tested to have the following characteristics: Vickers hardness ≥ 15 GPa; fracture toughness ≥ 4.2 MPa·m 1 / 2 ; Flexural strength ≥ 220MPa; Electrical conductivity ≥ 6×10 6 S / m; thermal conductivity ≥70W / (m·K); bulk density ≥4.55g / cm 3 .

[0027] Therefore, the boride-based composite ceramic electrode for an electric arc furnace prepared by the present invention has good wear resistance, excellent fracture toughness, high electrical conductivity and excellent thermal conductivity. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with specific implementation modes, but is not intended to limit the protection scope thereof.

[0029] A boride zirconium-based composite ceramic electrode for an electric arc furnace and a preparation method thereof. The preparation method described in this specific embodiment is:

[0030] Step 1: First, 85-95wt% of zirconium boride powder, 2-5wt% of zirconium carbide powder, 2.5-8wt% of silicon powder and 0.5-2wt% of tungsten powder are mixed, and then ball milled for 8-10 hours with a ball mill, and dried to obtain a composite powder.

[0031] Step 2: Pressing the composite powder into a shape under the condition of 100-120 MPa, and then cold isostatic pressing to obtain a ceramic body.

[0032] Step 3: placing the ceramic body in a vacuum induction furnace for vacuum induction sintering to obtain a zirconium boride-based composite ceramic electrode for an electric arc furnace.

[0033] The vacuum induction sintering process is as follows: first open the circulating water valve, then turn on the induction furnace power supply, and at a vacuum degree of 10 -2 ~10 -1 MPa, first heat to 800-900℃ at a power of 8-15kw, then heat to 1500-1600℃ at a power of 16-20kw, keep warm for 0.5-1.5h, turn off the power of the induction furnace, keep the circulating water valve open for 2-5h, and then close the circulating water valve.

[0034] The ball milling process is as follows: the rotation speed is 600-800 rpm, the ball milling medium is anhydrous ethanol, the grinding ball material is zirconium oxide, and the mass ratio of grinding ball to mixed powder is 1-4:1.

[0035] The cold isostatic pressing process:

[0036] First, increase the pressure at the following rates: increase the pressure to 30-50MPa at a rate of 0.1-4MPa / s, increase the pressure to 60-80MPa at a rate of 0.1-5MPa / s, increase the pressure to 90-110MPa at a rate of 0.1-10MPa / s, increase the pressure to 120-140MPa at a rate of 0.1-6MPa / s, increase the pressure to 150-200MPa at a rate of 0.1-8MPa / s, and maintain the pressure for 3-5min;

[0037] Then reduce the pressure at the following rates in sequence: reduce the pressure to 120-140MPa at a rate of 0.1-5MPa / s, reduce the pressure to 90-110MPa at a rate of 0.1-6MPa / s, reduce the pressure to 60-80MPa at a rate of 0.1-8MPa / s, reduce the pressure to 30-50MPa at a rate of 0.1-5MPa / s, reduce the pressure to 2MPa at a rate of 0.1-5MPa / s, and unload to normal pressure.

[0038] In this specific implementation mode:

[0039] The particle size of the zirconium boride powder is 1 to 3 μm; the purity of the zirconium boride powder is 99.9%;

[0040] The particle size of the zirconium carbide powder is 1 to 3 μm, and the purity of the zirconium carbide powder is 99%;

[0041] The particle size of the silicon powder is 1 to 5 μm, and the purity of the silicon powder is 99%;

[0042] The particle size of the tungsten powder is 1-5 μm, and the purity of the tungsten powder is 99.9 t%.

[0043] This will not be described in detail in the embodiments.

[0044] Example 1

[0045] A zirconium boride-based composite ceramic electrode for an electric arc furnace and a preparation method thereof. The preparation method described in this embodiment is:

[0046] Step 1: first mix 85wt% of zirconium boride powder, 5wt% of zirconium carbide powder, 8wt% of silicon powder and 2wt% of tungsten powder, then use a ball mill to mill for 8h, and dry to obtain a composite powder.

[0047] Step 2: Pressing the composite powder into a shape under 100 MPa, and then cold isostatic pressing to obtain a ceramic body.

[0048] Step 3: placing the ceramic body in a vacuum induction furnace for vacuum induction sintering to obtain a zirconium boride-based composite ceramic electrode for an electric arc furnace.

[0049] The vacuum induction sintering process is as follows: first open the circulating water valve, then turn on the induction furnace power supply, and at a vacuum degree of 10 -2 MPa, first heat to 800℃ at 8kw, then heat to 1500℃ at 16kw, keep warm for 0.5h, turn off the power of the induction furnace, keep the circulating water valve open for 2h, and then close the circulating water valve.

[0050] The ball milling process is as follows: the rotation speed is 600 rpm, the ball milling medium is anhydrous ethanol, the grinding ball material is zirconium oxide, and the mass ratio of grinding ball to mixed powder is 1:1.

[0051] The cold isostatic pressing process:

[0052] First, the pressure was increased at the following rates: 0.1 MPa / s to 30 MPa, 0.1 MPa / s to 60 MPa, 0.1 MPa / s to 90 MPa, 0.1 MPa / s to 120 MPa, 0.1 MPa / s to 150 MPa, and the pressure was maintained for 3 min.

[0053] The pressure was then reduced at the following rates in sequence: 0.1 MPa / s to 140 MPa, 0.1 MPa / s to 110 MPa, 0.1 MPa / s to 80 MPa, 0.1 MPa / s to 50 MPa, 0.1 MPa / s to 2 MPa, and then unloaded to normal pressure.

[0054] The boride zirconium-based composite ceramic electrode for arc furnace prepared in this embodiment is tested to have a Vickers hardness of 15.1 GPa and a fracture toughness of 4.6 MPa·m 1 / 2 ; Flexural strength is 239MPa; Electrical conductivity is 6.1×10 6 S / m; thermal conductivity is 75.5W / (m·K); volume density is 4.58g / cm 3 .

[0055] Example 2

[0056] A zirconium boride-based composite ceramic electrode for an electric arc furnace and a preparation method thereof. The preparation method described in this embodiment is:

[0057] Step 1: firstly mix 89wt% of zirconium boride powder, 4wt% of zirconium carbide powder, 5.5wt% of silicon powder and 1.5wt% of tungsten powder, then use a ball mill to mill for 9h, and dry to obtain a composite powder.

[0058] Step 2: Pressing the composite powder into a shape under 110 MPa, and then cold isostatic pressing to obtain a ceramic body.

[0059] Step 3: placing the ceramic body in a vacuum induction furnace for vacuum induction sintering to obtain a zirconium boride-based composite ceramic electrode for an electric arc furnace.

[0060] The vacuum induction sintering process is as follows: first open the circulating water valve, then turn on the induction furnace power supply, and at a vacuum degree of 10 -2 MPa, first heat to 830℃ at a power of 10kw, then heat to 1550℃ at a power of 18kw, keep warm for 0.8h, turn off the power of the induction furnace, keep the circulating water valve open for 3h, and then close the circulating water valve.

[0061] The ball milling process is as follows: the rotation speed is 700 rpm, the ball milling medium is anhydrous ethanol, the grinding ball material is zirconium oxide, and the mass ratio of grinding ball to mixed powder is 2:1.

[0062] The cold isostatic pressing process:

[0063] First, the pressure was increased at the following rates: 1 MPa / s to 40 MPa, 2 MPa / s to 70 MPa, 4 MPa / s to 100 MPa, 2 MPa / s to 130 MPa, 3 MPa / s to 165 MPa, and the pressure was maintained for 4 min.

[0064] The pressure was then reduced at the following rates: 2 MPa / s to 130 MPa, 2 MPa / s to 100 MPa, 3 MPa / s to 70 MPa, 2 MPa / s to 40 MPa, 2 MPa / s to 2 MPa, and then unloaded to normal pressure.

[0065] The boride zirconium-based composite ceramic electrode for arc furnace prepared in this embodiment is tested to have a Vickers hardness of 15.8 GPa and a fracture toughness of 4.3 MPa·m 1 / 2 ; Flexural strength is 235MPa; Electrical conductivity is 6.5×10 6 S / m; thermal conductivity is 73.7W / (m·K); volume density is 4.64g / cm 3 .

[0066] Example 3

[0067] A zirconium boride-based composite ceramic electrode for an electric arc furnace and a preparation method thereof. The preparation method described in this embodiment is:

[0068] Step 1: firstly mix 93wt% of zirconium boride powder, 3wt% of zirconium carbide powder, 3wt% of silicon powder and 1wt% of tungsten powder, then use a ball mill to mill for 9.5h, and dry to obtain a composite powder.

[0069] Step 2: Pressing the composite powder into a shape under 115 MPa, and then cold isostatic pressing to obtain a ceramic body.

[0070] Step 3: placing the ceramic body in a vacuum induction furnace for vacuum induction sintering to obtain a zirconium boride-based composite ceramic electrode for an electric arc furnace.

[0071] The vacuum induction sintering process is as follows: first open the circulating water valve, then turn on the induction furnace power supply, and at a vacuum degree of 10 -1 MPa, first heat to 860℃ at 13kw, then heat to 1580℃ at 19kw, keep warm for 1.2h, turn off the power of the induction furnace, keep the circulating water valve open for 4h, and then close the circulating water valve.

[0072] The ball milling process is as follows: the rotation speed is 750 rpm, the ball milling medium is anhydrous ethanol, the grinding ball material is zirconium oxide, and the mass ratio of grinding ball to mixed powder is 3:1.

[0073] The cold isostatic pressing process:

[0074] First, the pressure was increased at the following rates: 2 MPa / s to 45 MPa, 4 MPa / s to 75 MPa, 7 MPa / s to 105 MPa, 4 MPa / s to 135 MPa, and 5 MPa / s to 180 MPa, and the pressure was maintained for 3.5 min.

[0075] The pressure was then reduced at the following rates: 3 MPa / s to 125 MPa, 4 MPa / s to 95 MPa, 5 MPa / s to 65 MPa, 3 MPa / s to 35 MPa, 3 MPa / s to 2 MPa, and then unloaded to normal pressure.

[0076] The boride zirconium-based composite ceramic electrode for arc furnace prepared in this embodiment is tested to have a Vickers hardness of 15.3 GPa and a fracture toughness of 4.5 MPa·m 1 / 2 ; Flexural strength is 229MPa; Electrical conductivity is 6.9×10 6 S / m; thermal conductivity is 72.2W / (m·K); volume density is 4.67g / cm 3.

[0077] Example 4

[0078] A zirconium boride-based composite ceramic electrode for an electric arc furnace and a preparation method thereof. The preparation method described in this embodiment is:

[0079] Step 1: firstly mix 95wt% of zirconium boride powder, 2wt% of zirconium carbide powder, 2.5wt% of silicon powder and 0.5wt% of tungsten powder, then use a ball mill to mill for 10 hours, and dry to obtain a composite powder.

[0080] Step 2: Pressing the composite powder into a shape under 120 MPa, and then cold isostatic pressing to obtain a ceramic body.

[0081] Step 3: placing the ceramic body in a vacuum induction furnace for vacuum induction sintering to obtain a zirconium boride-based composite ceramic electrode for an electric arc furnace.

[0082] The vacuum induction sintering process is as follows: first open the circulating water valve, then turn on the induction furnace power supply, and at a vacuum degree of 10 -1 MPa, first heat to 900℃ at 15kw, then heat to 1600℃ at 20kw, keep warm for 1.5h, turn off the power of the induction furnace, keep the circulating water valve open for 5h, and then close the circulating water valve.

[0083] The ball milling process is as follows: the rotation speed is 800 rpm, the ball milling medium is anhydrous ethanol, the grinding ball material is zirconium oxide, and the mass ratio of grinding ball to mixed powder is 4:1.

[0084] The cold isostatic pressing process:

[0085] First, the pressure was increased at the following rates: 4 MPa / s to 50 MPa, 5 MPa / s to 80 MPa, 10 MPa / s to 110 MPa, 6 MPa / s to 140 MPa, and 8 MPa / s to 200 MPa, and the pressure was maintained for 5 min.

[0086] The pressure was then reduced at the following rates: 5 MPa / s to 120 MPa, 6 MPa / s to 90 MPa, 8 MPa / s to 60 MPa, 5 MPa / s to 30 MPa, 5 MPa / s to 2 MPa, and then unloaded to normal pressure.

[0087] The boride zirconium-based composite ceramic electrode for arc furnace prepared in this embodiment was tested to have a Vickers hardness of 16.3 GPa and a fracture toughness of 4.2 MPa·m 1 / 2 ; Flexural strength is 221MPa; Electrical conductivity is 7.1×106 S / m; thermal conductivity is 71.8W / (m·K); volume density is 4.72g / cm 3 .

[0088] Compared with the prior art, this specific implementation has the following positive effects:

[0089] (1) This specific implementation method makes full use of the high conductivity of the zirconium boride material itself, and utilizes the reactivity of zirconium carbide powder, silicon powder and tungsten powder at high temperature to adjust the in-situ formation of zirconium-tungsten alloy, zirconium silicide and silicon carbide and other bonding phases between the zirconium boride powder particles, thereby synergistically improving the electrical conductivity and thermal conductivity of the zirconium boride-based composite ceramic electrode for electric arc furnaces. Therefore, the zirconium boride-based composite ceramic electrode for electric arc furnaces prepared in this specific implementation method has high electrical conductivity and excellent thermal conductivity.

[0090] (2) This specific embodiment utilizes the reaction between zirconium carbide powder, silicon powder and tungsten powder during vacuum induction sintering to form zirconium-tungsten alloy, zirconium silicide and silicon carbide in situ between zirconium boride particles, thereby strengthening the bonding between zirconium boride powder particles; and utilizes the volume deformation during the reaction process to adjust the pore structure between particles and the densification behavior of material sintering. Therefore, the zirconium boride-based composite ceramic electrode for electric arc furnaces prepared in this specific embodiment has excellent fracture toughness and good wear resistance.

[0091] The boride zirconium-based composite ceramic electrode for arc furnace prepared in this specific embodiment is tested as follows: Vickers hardness ≥ 15 GPa; fracture toughness ≥ 4.2 MPa·m 1 / 2 ; Flexural strength ≥ 220MPa; Electrical conductivity ≥ 6×10 6 S / m; thermal conductivity ≥70W / (m·K); bulk density ≥4.55g / cm 3 .

[0092] The test standards of the performance indicators involved in the embodiments of this specific implementation method are as follows: Vickers hardness is measured according to the national standard GB / T16534-2009; fracture toughness is measured according to the GB / T23806-2009 standard; flexural strength is measured according to the GB / T4741-1999 standard; electrical conductivity is measured according to the GB / T11007-2008 standard; thermal conductivity is measured according to the GB / T5990-2021 standard; and bulk density is measured according to GB / T2999-2016;

[0093] Therefore, the boride-based zirconium composite ceramic electrode for an electric arc furnace prepared in this specific embodiment has good wear resistance, excellent fracture toughness, high electrical conductivity and excellent thermal conductivity.

Claims

1. A method for preparing a zirconium boride-based composite ceramic electrode for an electric arc furnace, characterized in that The steps of the preparation method are: Step 1, firstly mix 85-95wt% of zirconium boride powder, 2-5wt% of zirconium carbide powder, 2.5-8wt% of silicon powder and 0.5-2wt% of tungsten powder, then use a ball mill to mill for 8-10 hours, and dry to obtain a composite powder; Step 2, pressing the composite powder under 100-120 MPa, and then cold isostatic pressing to obtain a ceramic body; Step 3, placing the ceramic body in a vacuum induction furnace for vacuum induction sintering to obtain a zirconium boride-based composite ceramic electrode for an electric arc furnace; The vacuum induction sintering process is as follows: first open the circulating water valve, then turn on the induction furnace power supply, and at a vacuum degree of 10 -2 ~10 -1 MPa, first heat to 800-900℃ at a power of 8-15kw, then heat to 1500-1600℃ at a power of 16-20kw, keep warm for 0.5-1.5h, turn off the power of the induction furnace, keep the circulating water valve open for 2-5h, and then close the circulating water valve.

2. The method for preparing the zirconium boride-based composite ceramic electrode for electric arc furnace according to claim 1, characterized in that The particle size of the zirconium boride powder is 1-3 μm; the purity of the zirconium boride powder is 99.9%.

3. The method for preparing the zirconium boride-based composite ceramic electrode for electric arc furnace according to claim 1, characterized in that The particle size of the zirconium carbide powder is 1-3 μm, and the purity of the zirconium carbide powder is 99%.

4. The method for preparing the zirconium boride-based composite ceramic electrode for electric arc furnace according to claim 1, characterized in that The particle size of the silicon powder is 1-5 μm, and the purity of the silicon powder is 99%.

5. The method for preparing the zirconium boride-based composite ceramic electrode for electric arc furnace according to claim 1, characterized in that The particle size of the tungsten powder is 1-5 μm, and the purity of the tungsten powder is 99.9%.

6. The method for preparing the zirconium boride-based composite ceramic electrode for electric arc furnace according to claim 1, characterized in that The ball milling process is as follows: the rotation speed is 600-800 rpm, the ball milling medium is anhydrous ethanol, the grinding ball material is zirconium oxide, and the mass ratio of grinding ball to mixed powder is 1-4:

1.

7. The method for preparing the zirconium boride-based composite ceramic electrode for electric arc furnace according to claim 1, characterized in that The cold isostatic pressing process: First, increase the pressure at the following rates: increase the pressure to 30-50MPa at a rate of 0.1-4MPa / s, increase the pressure to 60-80MPa at a rate of 0.1-5MPa / s, increase the pressure to 90-110MPa at a rate of 0.1-10MPa / s, increase the pressure to 120-140MPa at a rate of 0.1-6MPa / s, increase the pressure to 150-200MPa at a rate of 0.1-8MPa / s, and maintain the pressure for 3-5min; Then reduce the pressure at the following rates in sequence: reduce the pressure to 120-140MPa at a rate of 0.1-5MPa / s, reduce the pressure to 90-110MPa at a rate of 0.1-6MPa / s, reduce the pressure to 60-80MPa at a rate of 0.1-8MPa / s, reduce the pressure to 30-50MPa at a rate of 0.1-5MPa / s, reduce the pressure to 2MPa at a rate of 0.1-5MPa / s, and unload to normal pressure.

8. A zirconium boride-based composite ceramic electrode for an electric arc furnace, characterized in that The zirconium boride-based composite ceramic electrode for an electric arc furnace is a zirconium boride-based composite ceramic electrode for an electric arc furnace prepared according to the zirconium boride-based composite ceramic electrode for an electric arc furnace and the preparation method thereof according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Graphite electrode of electric arc furnace

    CN209120506U

  • Graphite electrode for electric arc furnace

    CN212482127U

  • Graphite electrode of electric arc furnace

    CN212692546U

  • Method for sintering zirconium diboride ceramic material

    CN103011829A

  • High-strength and good-abrasion-resistance zirconium carbide ceramic material and preparing method thereof

    CN105016732A